Potent CYP3A4 Inhibitors Derived from Dillapiol and Sesamol - Carballo Arce, Ana Francis (2019)
Synthesis of 50 analogues of the natural insecticide synergists, dillapiol and sesamol, is reported. These were evaluated as potential insecticide synergists based on their inhibition of human CYP3A4. The most potent inhibitors have a relatively large hydrophobic substituent at either position 5 or 6 of these molecules. For example, 5-(benzyloxy)-6-(3- phenylsulfonyl)propyl)benzo[d][1,3]dioxole (18) and the diphenyl acetate of (6,7-dimethoxybenzo[d][1,3]dioxol-5-yl)propan1-ol (5n) show inhibitory concentrations for 50% activity IC50 values of 0.086 and 0.2 μM, respectively. These compounds are 106 and 46 times more potent than dillapiol whose IC50 for the inhibition of CYP3A4 is 9.2 μM. The ortho-chloro analogue (8f), whose activity is 86 times the activity of dillapiol, is the most potent of the fourteen 5-(benzyloxy-6-(2 propenyl)benzo[d][1,3]dioxoles prepared for this study